Association between Picky Eater Behavior with Stunting among Preschool Children in Surabaya - Novita Eka Hardini; Wirjatmadi, Bambang (Media Gizi Indonesia, 2024)
Stunting is one of the main nutritional problems in Indonesia. Stunting in children can be caused by various things, one of the problems is picky eater behavior which often appear at preschool age. The purpose of this study was to analyze the relationship between picky eater behavior and stunting in preschool children. The methods of this study used case control design, and for the sample selection used simple random sampling technique. The population of this study was all students in PG-TK Al Irsyad Surabaya and the sample for each case and control group was 15 respondents. Nutritional status was measured using the parameters height for age (H/A) and picky eater behavior using the Children's Eating Behavior Questionnaire (CEBQ). Data was analyzed using chi-square test. Most respondents have picky eater behavior and stunting (93.3%), followed by children with picky eater behavior and not stunting (53.3%). The results of statistical tests show that there is a relationship between stunting and picky eater behavior (p-value = 0.035). Additionally, children with picky eater behavior also have a bigger risk of stunting than children who were not (OR 12.250). So it could be concluded that stunting can be caused by various factors, one of which is picky eater behavior. The recommendation for parents to prevent picky eater behavior and stunting is they can try to use responsive feeding technique, so that children can develop good eating habits, and introduce a variety of foods since childhood.